Contextual Teaching-Learning dalam Media Digital: Studi pada Channel YouTube 'Arab Podcasts' - Simon, Anis Shalatin (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
This study analyzes the application of Contextual Teaching and Learning (CTL) elements in Arabic language learning videos on the Arab Podcast YouTube channel. The research method used is qualitative descriptive with content analysis of videos that focus on speaking, listening, reading, and writing skills. The results show that CTL elements such as constructivism have been well implemented, especially through the relevance of the material to the context of learners' daily lives. However, other elements such as inquiry, reflection, authentic assessment, and learning community are still not optimal. Videos tend to be one-way, lacking in facilitating collaboration between learners or independent exploration of concepts. In addition, authentic assessments that support the application of skills in real-life situations.